Analisis Pengaruh Tingkat Pendidikan, Keterampilan, Tingkat Pendapatan Dan Tanggungan Keluarga Terhadap Kemiskinan Di Desa Mas-Mas Kecamatan Batukliang Utara Kabupaten Lombok Tengah - Rohaeniah Zein; Siti Raehanun (Universitas Hamzanwadi, 2019)
The purpose of this study was to determine the effect of education level, skills, income level and family dependency simultaneously on poverty in Mas-Mas Village, North Batukliang District, Central Lombok Regency. To determine the effect of education level, skills, income level and partial family dependence on poverty in Mas-Mas Village, North Batukliang District, Central Lombok Regency. This type of research is quantitative research, the sampling technique used in this study uses proportional sampling The data collection techniques used are using questionnaires and documentationThe results of the study show that simulltan influences the level of education, skills, income level and family dependency simultaneously or jointly on poverty in Mas-Mas Village. This is evident from the value of Fcount Ftable (3,475 2,48). The magnitude of the influence of the four variables on poverty in Mas-Mas Village is shown by R Square which is equal to 0.138 or 13.8% and the remaining 86.2% is affected by other variables not included in this study. Multiple correlations simultaneously indicate that there is a low correlation between education level, skills, income level and family dependence on poverty in Mas-Mas Village, North Batukliang Subdistrict, Central Lombok Regency in 2019. Partially, the education and skill level variables have no influence significant impact on poverty in Mas-Mas Village. This can be seen from the value of tcount t table (0.196 1.98 and 1.514 1.98). While income level variables have a positive and significant effect on poverty in Mas-Mas Village. This can be seen from the tcount t table (2.689 1.98) and so with the family dependent variable has a negative and significant effect on poverty in Mas-Mas Village. This can be seen from the value of -thitung -ttable (-2,614 -1,98)